Spectral characteristics of dissolved organic matter in sediment pore water from Pearl River Estuary - Xu, Yang; Li, Penghui; Zhang, Chuanlun; Wang, Peng (Science China. Earth sciences, 2021)
As key parts of land-sea transition zones, estuary ecosystems play a very important role in the ocean carbon cycle processes. The sources, degradation, and preservation of dissolved organic matter (DOM) in estuaries have long been the subject of intense study. To examine the aforementioned issues, this study examined three-dimensional fluorescence spectroscopy and ultraviolet-visible absorption spectroscopy to determine the spatial distribution and sources of DOM in the pore water of three sedimentary cores from the Pearl River Estuary (S1, S2 and S3, with increasing salinity). Using the parallel factor analysis (PARAFAC) method to analyze the three-dimensional fluorescence spectrum data, five fluorescent components were obtained—three humic-like components (C1, C3, and C4), and two protein-like components (C2 and C5). C2 exhibited a significant positive correlation with the sediment microbial deoxyribose nucleic acid (DNA) concentration ( R 2 =0.69, P < 0.01), indicating that the protein-like component C2 might be derived from the catabolism of in situ microbes. C5 displayed a relatively weak correlation with DNA concentration ( R 2 =0.40, P < 0.05), presumably due to the incorporation of phenolic compounds, which have a fluorescence peak very similar to that of protein-like components. The source of humic-like fluorescent components is extremely complex. The content at station S1 was relatively high (1.45–8.83 R.U.), which implies that terrestrial inputs had a significant influence. The three humic-like components showed similar distributions at S2 and S3, and the fluorescence intensity was rather low; this result indicates that the DOM at these two stations was more likely affected by the metabolism of algae and microorganisms. The humification index (HIX) and the fluorescence intensity of protein-like components increased and decreased, respectively, with depth. There was a significant positive correlation between the relative content of protein-like components and the spectral slope ratio ( S R ), which indicates that DOM transitioned from low-molecular-weight protein-like components in the surface sediment to high-molecular-weight humic-like components in the subsurface. This study provides valuable information for understanding the pore water size/reactivity (PWSR) model of DOM and its biochemical processes occurring in estuary sediments.